2009
DOI: 10.1016/j.baae.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Local–regional richness relationship in fouling assemblages – Effects of succession

Abstract: The number of species in a local habitat depends on local and regional processes. One common approach to explore ecological saturation of local richness has been to plot local versus regional richness. We expand this approach by incorporating two dimensions of diversity -taxonomic and functional -and different successional ages of marine fouling communities. In four different biogeographic regions (Mediterranean Sea, NE Atlantic, Western Baltic Sea and North Sea) 60 experimental units made from artificial subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In 2006 we initiated a NIS monitoring program in a local marina located along the South-eastern coast of Madeira Island [17,54]. We later expanded this study by adding a second marina in 2010, and two additional marinas in 2013 [16,18].…”
Section: Methodsmentioning
confidence: 99%
“…In 2006 we initiated a NIS monitoring program in a local marina located along the South-eastern coast of Madeira Island [17,54]. We later expanded this study by adding a second marina in 2010, and two additional marinas in 2013 [16,18].…”
Section: Methodsmentioning
confidence: 99%
“…The latter definition proved a major step forward and allowed ecologists to weigh the probability that a species would be included in a community's species pool and to estimate its geographical extent (Graves & Rahbek, ; Lessard et al ., ). Since then, temporal extent has been recognized as an important factor (dispersal or survival over time) that can lead to changes in species pool size (Munguia, ; Starzomski et al ., ; Canning‐Clode et al ., ; White & Hurlbert, ; Cornell & Harrison, ) but has remained notoriously difficult to integrate into species pools definitions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, landscape-level experimental tests of how successional dynamics alter LSR-RSR relationships are challenging because locations and regions must be manipulated over large spatial scales and long time periods relative to the organisms of interest. To date, the best experimental tests have come from studies that have either manipulated local communities within naturally varying regional species pool sizes (Munguia 2004, Canning-Clode et al 2009) or have manipulated both local and regional richness in mesocosm experiments (Starzomski et al 2008). At larger scales, there has been only one landscape experimental test of successional LSR-RSR relationships, to our knowledge, which was conducted within a timber harvesting study (Belote et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The pervasive roles of disturbance and succession for community assembly suggest that temporal dynamics may play a key role in observed LSR-RSR relationships. Theoretical work (Mouquet et al 2003) and a handful of empirical studies (Munguia 2004, Starzomski et al 2008, Belote et al 2009, Canning-Clode et al 2009) have also suggested successional dynamics can impact LSR-RSR relationships, due to the decoupling of dispersal and competition by local disturbances. Theory predicts that initially after a disturbance, competitive dynamics become disrupted locally and that ensuing colonization from the regional species pool occurs at Manuscript received 4 October 2011; accepted 22 November 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation